2002
DOI: 10.1021/ac0259257
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Isotopic Composition and Atomic Weight of Commercial Zinc Using Inductively Coupled Plasma Mass Spectrometry

Abstract: Inductively coupled plasma mass spectrometry is introduced as a method for determining the absolute isotopic composition of zinc. The high ionization efficiency and time-independent characteristics of the mass spectrometry permit the absolute isotopic composition of high ionization potential elements. The mass discrimination of the instrument is calibrated by synthetic isotope mixtures prepared from highly enriched isotopes of zinc. The resulting isotope ratios yield atomic percents of 64Zn, 49.188 +/- 0.030; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 27 publications
(45 reference statements)
3
39
0
10
Order By: Relevance
“…The authors calibrated their instrument using synthetic mixtures of highly enriched Zn isotopes. Their value for A r (Zn) measured from the isotope reference material IRMM-3702 is 65.377 77 (22), which is significantly different from the previous IUPAC value of 65.409(4) [1,2]. The latter is based on a calibrated measurement by Chang et al using TIMS [21].…”
Section: Zincmentioning
confidence: 72%
See 2 more Smart Citations
“…The authors calibrated their instrument using synthetic mixtures of highly enriched Zn isotopes. Their value for A r (Zn) measured from the isotope reference material IRMM-3702 is 65.377 77 (22), which is significantly different from the previous IUPAC value of 65.409(4) [1,2]. The latter is based on a calibrated measurement by Chang et al using TIMS [21].…”
Section: Zincmentioning
confidence: 72%
“…The latter is based on a calibrated measurement by Chang et al using TIMS [21]. A calibrated MC-ICP-MS measurement by Tanimizu et al [22] found an atomic weight of Zn of 65.3756 (40), also significantly different from the earlier value [21]. It is important to note that the atomic weight of Zn of 65.377(3) determined much earlier using coulometric techniques [23] is in good agreement with the measurement by Ponzevera et al [20] and Tanimizu et al [22].…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the routine analysis of natural samples, the Pb isotope ratios to be measured are different one by one, and inevitably the Pb isotope composition of the remaining Pb signal memory after 5 minute washout should vary significantly. If an analyzed sample has an extreme Pb isotopic composition, the memory may affect the measured value of the next sample like the case of zinc in double-spike analysis (Tanimizu et al, 2002), although we had shown that the level of the Pb memory is less than 0.01% of the sample signal in usual analysis (Fig. 1) Zindler and Hart, 1986).…”
Section: Confirmation Of Matrix-and Memory-independence Of the Pb Isomentioning
confidence: 76%
“…The mass bias factor of the dopant in each sample and standard was calculated using the measured ratio (R measured ) and its natural abundance ratio (R true ) taken from literature. 19,20 In the case of Cu acting as dopant:…”
Section: Corrections For Mass Biasmentioning
confidence: 99%